The Effect of Increasing Immigration Enforcement on the Labor Supply of High-Skilled Citizen Women - Chloe N. East; Andrea Velasquez (Institute of Labor Economics (IZA), 2018)
Recent decades have seen a surge in local interior immigration enforcement. In this paper we examine a little discussed, but potentially important, spillover effect of enforcement policies: changes in high-skilled citizen women's labor supply due to changes in the cost of outsourcing household production. Undocumented immigrants disproportionately supply household services - e.g. as maids, cooks, child care workers, and gardeners - so the price of outsourcing these services is expected to rise in response to enforcement. Combining data on the timing and location of these enforcement policies, with data on labor supply from the American Community Survey over 2005-2012, we implement a difference-in-difference approach with location and year fixed effects to take advantage of the staggered implementation of these policies. We find that an increase in intensity of immigration enforcement in a local area reduced the labor supply of citizen college- educated women with children. Several results suggest that changes in the price of outsourcing are driving these results: 1) we see an increase in time spent on household production tasks among mothers in the American Time Use Survey, 2) we confirm that there is an increase in the wages of household workers, and 3) we see no similar effects for high-skilled men or women without children. This indicates there are important unintended consequences of enforcement policies on high-skilled citizen mothers' ability to work.
Keywords: F22; J2; K37; J16; 330; immigration; labor supply; gender